Influence of various trace metallic additions and reinforcements on A319 and A356 alloys—a review. Issue 1 (1st January 2022) - Srinivas, D; M C, Gowrishankar; Hiremath, Pavan; Sharma, Sathyashankara; Shettar, Manjunath; P K, Jayashree
Abstract: In this article, aspects related to A319 (AlSi5Cu3) and A356 (AlSi7Mg) alloy are covered owing to their prominent role in the automotive and aerospace industries. It is important to collect overall information related to these alloys and process them so that the material properties can be improved easily in the future by the addition of various trace metallic elements such as Mg, Sr, Sc, Cu, No, Ti, B, Mn, V, Zr and Ca. The addition of Mg (up to 0.45 wt.%) has been identified as the best way to improve tensile properties. It has also been identified that Sr addition modifies eutectic Si morphology and increases tensile properties. The presence of Cu causes the formation of Al2 Cu which must be taken care of with proper treatments. Ni addition reduces the effect of Fe phases, and Sc addition improves the tensile properties. Various methods that can be used to produce the alloys mentioned above, related heat treatment processes, and parameters were briefly discussed. The influences of various reinforcements, modifiers, and grain refiners are presented. Solution heat treatment is implemented to dissolve intermetallic phases and the various parameters for aging treatment, cooling rate, and temperature to be used to improve the mechanical properties are also discussed. Among the various heat treatment processes, two-stage solutionizing treatment outperforms single and triple stage treatment processes in terms of improving the mechanical properties.